EXPERIENCE OF PSYCHOLOGICAL READINESS FORMATION OF FUTURE DOCTORS FOR THE PROFESSIONAL ACTIVITIES - Smila, Natalya; Lazurenko Оlena (PSYCHOLOGICAL JOURNAL, 2017)
The problem of the formation of professional competence of future doctors is one of the most important in the field of professional medical education. The article studies main properties of psychological readiness formation of future doctors for the professional activities. The article is focused on theoretical and practical bases of the diagnostics of psychological readiness of future doctors for professional activities based on components and stages of its development. The paper theoretically grounded basic stages of development of psychological readiness for professional activities with account of age features of students. In particular highlighted the steps of psychological readiness: choosing a career, joining the study, adaptation to study, adaptation to professional activities. The structure of doctor’s psychological readiness for professional activities included the following six components: professional and intellectual, communicative, emotional, volitional, moral, dynamic, nervous and mental. The content and nature of components is confirmed with the use of expert evaluation. Main aspects of future doctors’ professional training at higher medical educational institutions are also described. Using empirical research the features and factors of psychological readiness for professional activity of future doctors were shown. Determined that all components of readiness develop gradually and reach its peak during the process of adaptation to professional activities. After summarizing the results of the factor analysis identified factors of psychological readiness of doctors to the profession at various stages of development. Today, there are available and used a variety of exercises, tasks, seminars, workshops aimed at the development of the professional competence of the student, which can be suggested as an additional material in the process of theoretical and practical training of future doctors in higher medical educational establishments. The concept of formation of psychological readiness formation of future doctors for the professional activities is suggested. Prospects and directions for future research were identified.